Feeding management and production factors affecting goat milk composition and quality. II. Physical and chemical properties and mineral content - Summer A.; Superchi P.; Sabbioni A.; Formaggioni P.; Mariani P. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Individual milk samples representing the overall morning milking were collected monthly (from April to September) from 24 Saanen goats, uniformly distributed into two herds in Northern Italy with the aim to evaluate the factors affecting physico-chemical properties and mineral content. Herds differed in feeding management system: Traditional and Total mixed ration (TMR). Herd type was related to milk chemical composition; compared to TMR, Traditional herd type improved dry matter content and lowered ash. Milk dry matter was related to fat, protein and lactose; ash was related to milk yield, fat and protein; freezing point was related to lactose, urea and fat. Ca, P and Mg contents were influenced by the herd type, with lower values in Traditional than in TMR. A positive relationship was found between: milk yield and P and K; protein and Ca, P, Mg and Na; lactose and Ca and P; somatic cells and Mg; pH and Na; urea and Na. A negative relationship was found between: protein and K; lactose and Na and K; pH and P. Potassium content was higher for primiparous goats and for single delivery goats. Keywords: Feeding management, production factors, physico-chemical properties, mineral content, goat milk.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)